Illocutionary Acts in Tetun Language Use during Multicultural Interactions at the Traditional Market of Biboki Anleu - Vincentius Mauk; Casimiro Relvas Amaral; Anselmus Yata Mones; Palmerya Ch. Sau (Nexus Publishing, 2026)
The multicultural traditional market in Biboki Anleu serves as a socio-economic interaction space where speakers from diverse ethnolinguistic backgrounds engage using Tetun as a lingua franca, revealing rich pragmatic dynamics. This study aims to identify and analyze the types of Tetun illocutionary acts in marketplace interactions and assess the role of Tetun in fostering multicultural communication and social solidarity. A qualitative approach was employed using participatory observation, in-depth interviews, and discourse analysis. Data were collected from real-time interactions between sellers and buyers in Biboki Anleu Market. Four dominant types of illocutionary acts were identified: directive, representative, expressive, and commissive. Language strategies reflected local politeness norms, pragmatic efficiency, and cultural adaptation. Tetun illocutionary acts function not only as transactional tools but also as mechanisms for reinforcing social identity and cultural integration. The findings contribute theoretically to regional language pragmatics and practically to multicultural market development and Tetun language preservation.